INVESTIGATION OF THE GEODYNAMIC PROCESS IN MASS TRANSFER ANOMALOUS ZONES - AZIMOV, O.; BUBLIAS, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of investigation of the geodynamic process for the depression morphosculptures by remote aerospace, geological, geomorphologic and geophysical methods have adduced. The Chornobyl Exclusion Zone territory has considered as an example. The morphosculptures were classified by the morphological types. The clear space and correlative connections between the unmasked landscape and emanation anomalies and the heterogeneities of geophysical fields have retraced.